National and gender stereotype on perceived managerial skills. - Lee, Bee Khim. (2008)
This resarch examines the effect of national and gender stereotypes in the opinion formation of managers from different nationalites. our questionnaire dealt with managers from US, Singapore and Vietnam. We used five managerial skills, namely, communication skills (CS), interpersonal skills (IS), aspiration-achievement skills (AS), problem-solving skills(PS) and leadership skills(LS) as a measure of the managerial effectiveness in this research. Over 350 questionnaires were distributed and completed by respondents from the three mentioned countries.